A longitudinal study of morning, evening, and night light intensities and nocturnal sleep quality in a working population. (3rd April 2022) - Amdisen, Lau; Daugaard, Stine; Vestergaard, Jesper Medom; Vested, Anne; Bonde, Jens Peter; Vistisen, Helene Tilma; Christoffersen, Jens; Garde, Anne Helene; Hansen, Åse Marie; Markvart, Jakob; Schlünssen, Vivi; Kolstad, Henrik Albert
ABSTRACT: We aimed to investigate whether higher light intensity in the morning is associated with better nocturnal sleep quality and whether higher light intensities in the evening or night have the opposite effect. Light intensity was recorded for 7 consecutive days across the year among 317 indoor and outdoor daytime workers in Denmark (55–56° N) equipped with a personal light recorder. Participants reported sleep quality after each nocturnal sleep. Sleep quality was measured using three parameters; disturbed sleep index, awakening index, and sleep onset latency. Associations between increasing light intensities and sleep quality were analyzed using mixed effects models with participant identity as a random effect. Overall, neither white nor blue light intensities during morning, evening, or night were associated with sleep quality, awakening, or sleep onset latency of the subsequent nocturnal sleep. However, secondary analyses suggested that artificial light during the morning and day contrary to solar light may increase vulnerability to evening light exposure. Altogether, we were not able to confirm that higher morning light intensity significantly improves self-reported sleep quality or that higher evening or night light intensities impair self-reported sleep quality at exposure levels encountered during daily life in a working population in Denmark. This suggests that light intensities alone are not important for sleep quality to a degree that it is distinguishable from other important parameters in daily life settings.